INTERPRETASI DATA SEISMIK DENGAN MENGGUNAKAN SOFTWARE KINGDOM 6.7.1 - mohammad hasib; Adi Susilo (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2020)
Seismic method can provide detailed information on the subsurface structure to determine the prospect / potential of hydrocarbons. There are few previous studies have used KINGDOM software in processing and interpreting seismic data to determine hydrocarbon potential. Therefore, in this study we provide an overview of how the KINGDOM software works which can be used as an option in processing and interpreting seismic data. This research area is the area of East Java basin. The data used are secondary data. The seismic data used is the final PSTM - STACK - SUKOWATI 3D. Extension is used in the form of SGY File. Selected area in interpretation is inline within range 6100 to 6500 (dimensionless) and crossline within range 12700 to 13000 (dimensionless), with the increment about 10. KINGDOM 6.7.1 software is used for seismic data processing. Interpretation of seismic data is done to obtain information from seismic data, to provide a conclusion that can be accounted by the analysis of all available information or data in order to determine the subsurface structure of the prospect to do the drilling. As for the 3D, the form of the anticline is seen with details like the shape of the anticline in general. The apparent anticline probably indicates the presence of hydrocarbons (oil and gas).